Pengaruh Model Pembelajaran Kooperatif "Think Pair Share" terhadap Hasil Belajar Bahasa Inggris - Nurul Badriyatul Muthoharoh (SAP (Susunan Artikel Pendidikan), 2017)
The aim of this research is to find out the difference between English learning outcomes of students taught using an expository method and those of students taught applying a cooperative model Think Pair Share (TPS). The sample of the research is 40 students divided into 2 groups, namely experimental group and control group. The research applies an experimental method and uses a simple random sampling technique. The research is expected to be beneficial for students, teachers, schools and researchers. The data analysis technique using “t-test” at significance level ? = 0.05 shows tobserved=2.893 and ttable = 2.0252. So, it can be concluded that students taught applying a cooperative model “Think Pair Share (TPS)” have higher English learning outcomes than those taught using an expository method